Increasing Interest in Learning Sociology Through Interactive Learning Media Kahoot! in Class XII Sociology 3 - Fadhilah, Muhammad Arif; Imran, Imran; Partiwi, Sri Uji; Sari, Ifa Meilyana; Harjanti, Diah Trismi (Universitas Tanjungpura, 2025)
This research was conducted with the aim of increasing students' interest in learning in sociology through the use of interactive learning media Kahoot! in class XII Sociology 3 SMA Negeri 8 Pontianak consisting of 37 students. The obstacles faced include a lack of interest in learning students and boredom in learning sociology. As a solution, the researcher chose to use the interactive media Kahoot! as an effort to increase students' interest in learning. The method used in this study is Classroom Action Research (PTK) which involves several stages, In cycle 1, the use of interactive media in learning was not yet complete, but when tested as an initial form, the results obtained were temporarily positive student responses marked by 42% of students participating in the learning process. So the researcher decided to continue the research to cycle 2. in cycles 2 and 3 each consists of 3 stages of research carried out by the researcher. Namely the planning stage which functions as steps as a procedural guide. Then the implementation stage which functions as the process of implementing interactive media in the form of Kahoot. The last stage is analysis and reflection as a process to review the effectiveness of learning using interactive kahoot! media in the learning system in class XII Sociology 3. Students have shown positive responses to the use of Kahoot! and find it interesting and fun. It can be concluded that the use of interactive learning media Kahoot! effective in increasing students' interest in learning in sociology. Based on the results of analysis and reflection in cycle 3 of the research, as many as 94% of students showed enthusiasm to participate in learning. This media is able to create a fun learning experience and reduce student boredom. It is recommended that sociology teachers consider using interactive media such as Kahoot! as an alternative strategy in increasing students' understanding and interest in learning in sociology subjects.